(untitled) (Al-Academy, 2016)
The search (floors and transparent role in the design studios satellite channels) and presented as a study-oriented, and the research aims to identify the role of flooring transparent spaces studios satellite channels and side performative and aesthetic, and formulas design to highlight the role floors transparent spaces studios satellite channels. And highlight the importance of research, particularly in its contribution to the clarification of the concept of the relationship between transparency and performing aesthetic treatments for floors by clarifying its role in the designs of the internal spaces of the studios, as well as his contribution to the founding of the theory of looking at the base of such concepts. To achieve the objectives of the research, the researcher based on the descriptive approach in the study, as the appropriate method to gain access to comprehensive coverage of the objectives of the research, has been selected samples is my intention, and based on the literature and studies on transparency in the internal spaces, and use the researcher is also the tool of research II (questionnaire), which included Astmartin has drawn questions from which adherents of workers in the channels and viewers of those channels, the analysis was designed questionnaire included several axes, and the most important: 1- shape and size of the internal space of the studio and achievable for the job (performance and beauty). 2 multiple layers of earth and its relationship to the extra dimension and motor insulation career and privacy. 3 color discrimination for flooring satellite channels and selected sections of the space. 4 ores and materials used in flooring studios and their impact in achieving transparency. Has resulted in the analysis process for the development of a set of conclusions and the most important: 1 that the internal floor space for studios satellite channels check in multiple career highs insulation and privacy between multiple studio spaces, and it adds a dimension to the physically and visually to the interior space of the studio. 2 that the plastic material may be used in the studio floor space and can be achieved along with the performative and aesthetic, as if the designer deal with these materials in order to serve the desired purpose in the floor space of the studios. The most important recommendations of the beneficiaries of the research that is being designed floor interior spaces for studios, satellite channels on as achieved by my performance and aesthetic vision through design verification purposes highest performance and beauty. During the design of the idea of what is required to perform advanced functionality and aesthetic expression and function of the flooring spaces studios satellite channels. The researcher suggested the study of modern electronic techniques and ways to employ them in the flooring studios satellite channels